Liquid Crystal Networks on Thermoplastics: Reprogrammable Photo‐Responsive Actuators. Issue 11 (30th January 2020) - Verpaalen, Rob C. P.; Pilz da Cunha, Marina; Engels, Tom A. P.; Debije, Michael G.; Schenning, Albert P. H. J.
Abstract: Arbitrary shape (re)programming is appealing for fabricating untethered shape‐morphing photo‐actuators with intricate configurations and features. We present re‐programmable light‐responsive thermoplastic actuators with arbitrary initial shapes through spray‐coating of polyethylene terephthalate (PET) with an azobenzene‐doped light‐responsive liquid crystal network (LCN). The initial geometry of the actuator is controlled by thermally shaping and fixing the thermoplastic PET, allowing arbitrary shapes, including origami‐like folds and left‐ and right‐handed helicity within a single sample. The thermally fixed geometries can be reversibly actuated through light exposure, with fast, reversible area‐specific actuation such as winding, unwinding and unfolding. By shape re‐programming, the same sample can be re‐designed and light‐actuated again. The strategy presented here demonstrates easy fabrication of mechanically robust, recyclable, photo‐responsive actuators with highly tuneable geometries and actuation modes. Abstract : Thermoplastic polyethylene terephthalate (PET) were spray‐coated with an azobenzene‐doped liquid‐crystal network (LCN). Arbitrary shapes are programmed by thermal shaping and fixing of PET, enabling untethered, area‐specific light response with origami‐like folds. The thermoplastic actuator demonstrates multi‐modal shape morphing in a single sample and can be re‐designed and light‐actuated repeatedly.